Applying The AIDA Framework to Website-Based Digital Communication: Public Engagement in Islamic Philanthropy - Sekar Apriliza; Nadahaniah Nadahaniah; Hazitun Nisa; Alfa Laila; ALI MUJASIR (Institut Agama Islam Negeri Pontianak, 2025)
Digital transformation has fundamentally reshaped communication practices in nonprofit organizations, requiring Islamic philanthropic institutions to adopt effective digital communication strategies to strengthen public engagement and sustain donor participation. Although previous studies have extensively examined digital fundraising and social media communication, limited attention has been given to the strategic role of organizational websites as integrated communication and engagement platforms. Addressing this gap, this study investigates how Dompet Dhuafa’s official website facilitates public engagement through digital communication strategies. A qualitative case study approach was employed using secondary data collected from academic literature, institutional reports, and systematic digital observation of the website. Data were analyzed through thematic analysis guided by the Attention–Interest–Desire–Action (AIDA) framework and the concept of public engagement. The findings reveal that the website functions not only as an information repository but also as an integrated engagement ecosystem that combines persuasive communication, transparent program reporting, interactive features, and seamless digital donation services. The implementation of AIDA is reflected in compelling visual content, well-structured program information, emotionally engaging narratives, and accessible call-to-action mechanisms that encourage user participation. Furthermore, financial transparency, impact reporting, and interactive communication channels including FAQs, contact forms, WhatsApp services, and social media integration enhance organizational credibility and foster public trust. The study contributes to the literature by extending the application of digital communication theory to website-based engagement within the context of Islamic philanthropy, an area that remains underexplored. Practically, the findings provide strategic insights for nonprofit organizations seeking to optimize websites as digital communication infrastructures that promote sustainable public engagement and strengthen long-term donor relationships.